2011
DOI: 10.5005/jp-journals-10024-1010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Levels of Interleukin-1β in Gingival Crevicular Fluid to the Clinical Parameters of Chronic Periodontitis

Abstract: Aim: Background and objectives: IL-1β is a potent stimulator of bone resorption and has been implicated in the pathogenesis of periodontal destruction. Therefore, this study was designed to compare the levels of IL-1β of chronic periodontitis patients with the healthy subjects. Another objective of this study was to correlate IL-1β levels with the clinical parameters of the periodontal disease progression. Methods: For this study, total 60 subjects were chosen (30healthy and 30-chronic periodontitis). Simplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
3
21
0
2
Order By: Relevance
“…In agreement with our findings, the increase in IL‐1β, IL‐8, MMP‐13, OPG, and osteoactivin levels in periodontitis patients has been previously described . Moreover, IL‐1β, IL‐8, and MMP‐13 levels increased in active sites compared with inactive sites from progressive periodontal disease .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our findings, the increase in IL‐1β, IL‐8, MMP‐13, OPG, and osteoactivin levels in periodontitis patients has been previously described . Moreover, IL‐1β, IL‐8, and MMP‐13 levels increased in active sites compared with inactive sites from progressive periodontal disease .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, IL‐1β, IL‐8, and MMP‐13 levels increased in active sites compared with inactive sites from progressive periodontal disease . IL‐1β is secreted primarily by macrophages after bacterial infection or tissue injury and participates in the pathogenesis of periodontal destruction, with IL‐1β levels in GCF correlating with the inflammatory status of periodontal disease . IL‐8 is considered an important mediator of recruitment and activation of human neutrophils and downregulated with periodontal therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that IL-1 β levels can be used as a good biomarker to differentiate between healthy and chronic periodontitis sites [12, 41, 51, 53, 98]. They can also be used to discriminate healthy subjects from patients with AgP [41, 51, 80, 99].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have assumed that formation of inappropriate cytokines results in protective immunity, whereas inappropriate cytokines result in tissue destruction and disease progression. 1,[3][4][5] Interleukin-18 is a proinflammatory cytokine derived from T cells and produced mainly by cells of Th1/Th0 phenotype but not cells of the Th2 phenotype. 4 In periodontal patients, IL-7, IL-8, IL12, IL-17, and IL-19 have been testified in both GCF and periodontal tissues.…”
Section: 5005/jp-journals-10024-2180mentioning
confidence: 99%